Advancing Heat Exchanger Technology in Textile Engineering Materials for Electric Vehicles through Additive Manufacturing - Dr. Ganesh S. Kakad; Dr. Sagar S. Gaddamwar (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The rapid evolution of electric vehicles (EVs) necessitates significant advancements in thermal management technologies to enhance efficiency, performance, and safety. This paper explores the innovative integration of heat exchanger technology with textile engineering materials, facilitated by additive manufacturing (AM) techniques. Traditional heat exchangers, while effective, often fall short in adapting to the specific needs of EV thermal management systems due to limitations in flexibility, weight, and design complexity. By leveraging the adaptable and lightweight properties of textiles, combined with the precision and customization capabilities of AM, this research aims to develop advanced heat exchangers that address these limitations. Textile engineering materials offer unique benefits, such as flexibility, lightweight characteristics, and potential for enhanced thermal conductivity through innovative treatments and composites. When integrated with heat exchanger technology, these materials can be utilized to create novel structures that enhance heat dissipation and improve overall thermal management in EVs. Additive manufacturing further augments this potential by enabling the precise fabrication of complex geometries and customized designs that traditional manufacturing techniques cannot achieve. The paper reviews current advancements in heat exchanger technologies, including air-cooled, liquid-cooled, and phase change material (PCM) systems, and examines how textile-based solutions can enhance these technologies. It discusses the application of AM in fabricating advanced textile-based heat exchangers, highlighting its advantages in design flexibility, material customization, and rapid prototyping. The integration of AM with textile engineering is explored as a means to overcome existing challenges such as material compatibility and manufacturing complexity. Future directions for research are identified, focusing on developing advanced textile materials with improved thermal properties, exploring sustainable practices, and optimizing the performance of textile-based heat exchangers in real-world EV applications. The paper concludes that this interdisciplinary approach has the potential to revolutionize thermal management in electric vehicles, leading to more efficient, adaptable, and high-performance systems that meet the evolving demands of the automotive industry.